Investigation of Antioxidants and Some Biochemical Parameters in Sheep and Cattle Infected With Toxoplasmosis - Jasim, Maysoon Mustapha; Al-Douri, Rasha Shamil Hussein (Academia Open, 2025)
The current study aimed to evaluate the effect of infection with Toxoplasmosis gondii in the serum and milk of sheep and cows on some enzymes and biochemical parameters. 200 samples from sheep and 125 samples from cows that suffered from miscarriages at different stages of pregnancy and were suspected of being infected with toxoplasmosis were collected from different areas of Salah Governorate. Using the latex agglutination test, it was found that the percentage of infection with toxoplasmosis in sheep is 47.5% and 33.6% in cows. According to the statistical results of biochemical tests, sheep and cows exposed to Toxoplasma showed an increase in glutathione peroxidase levels (GSH-PX) in their serums, whereas infection did not significantly affect the activity of creatine phosphokinase in sheep or cows, as did creatine phosphokinase. As a result of this infection, zinc levels in sheep and cows' serum were significantly decreased, which resulted in a significant increase in copper and phosphorus levels. Toxoplasma infection resulted in a decrease in milk parameters including protein and fat, as well as lactose in cow's milk, while it did not significantly change in sheep's milk compared to the control group. Highlights: Effect of Toxoplasma gondii on serum and milk biochemical parameters in livestock. Infection impact: Increased GSH-PX, decreased zinc, increased copper and phosphorus levels. Milk quality decline: Reduced protein, fat, and lactose in cows; minimal change in sheep. Keywords: toxoplasmosis, toxoplasmosis in sheep,Oxidation enzymes.